The Effect of Dielectric Permeability in Anisotropic Bending Spiral - Al-Gawagzeh, M. Y. (Elektronika ir Elektrotechnika, 2009)
This study shows that the assumption of geometric parameters of the spiral shaped of optical fiber leads to an exact solution for the fiber modes. Also it shows the possibility of changing the transfer parameters (attenuation and dispersion) into a better form. Spiral fibers are proven to be particularly efficient as they produce excellent confinement of the electromagnetic fields. The components of dielectric permeability tensor  ij according to the parameters  and  in the system of coordinates r,  is analyzed. The tensor components  ij dependences on the bend parameters R and  are calculated. Ill. 1, bibl. 9 (in English; summaries in English, Russian and Lithuanian).